CO2 electrolysis towards large scale operation: rational catalyst and electrolyte design for efficient flow-cell - Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (Chemical Communications, 2023)
The electrochemical CO2 reduction reaction (CO2RR) to renewable fuels/chemicals is a potential approach towards addressing the carbon neutral economy. To date, a comprehensive analysis of key performance indicators, such as an intrinsic property of catalyst, reaction environment and technological advancement in the flow cell, is limited. In this study, we discuss how the design of catalyst material, electrolyte and engineering gas diffusion electrode (GDE) could affect the CO2RR in a gas-fed flow cell. Significant emphasis is given to scale-up requirements, such as promising catalysts with a partial current density of >= 100 mA cm(-2) and high faradaic efficiency. Additional experimental hurdles and their potential solutions, as well as the best available protocols for data acquisition for catalyst activity evaluation, are listed. We believe this manuscript provides some insights into the making of catalysts and electrolytes in a rational manner along with the engineering of GDEs towards CO2RR.